Rotavirus hospitalizations among children <5 years of age—Tajikistan, 2013–2014. Issue 51 (14th December 2018) - Nazurdinov, Anvar B.; Azizov, Zafarjon A.; Tishkova, Farida; Turkov, Sohibnazar M.; Daniels, Danni S.; Leshem, Eyal
Highlights: Rotavirus surveillance in Tajik children aged <5 years was conducted during 2013–14. Among 2860 children enrolled and tested, 42% were positive for rotavirus. The predominant genotype G1P[8] accounted for 60% of genotyped cases. Abstract: Background: In January 2015, Tajikistan introduced the monovalent rotavirus vaccine into the national immunization program. Our objective was to estimate pre-vaccine burden of rotavirus-associated hospitalizations in children <5 years of age in Tajikistan. Methods: During January 2013–December 2014, active surveillance for acute gastroenteritis (AGE)-associated hospitalizations in children <5 years of age was conducted by sentinel surveillance site staff. Patients' demographic and clinical data were summarized and a stool sample was collected. An Enzyme Linked Immunosorbent Assay was used for diagnosis of rotavirus infection and subset of the specimens was sent for polymerase chain reaction (PCR) genotyping. Results: Of 2860 eligible children enrolled and tested, 1207 (42%) were positive for rotavirus. An increase in the number and proportion of rotavirus cases attributed to rotavirus season, with positivity rates >40%, was annually observed during June–September. The median age of rotavirus patients was 9 months and 939/1207 (78%) rotavirus patients were aged 6–23 months. Most (1097/1203; 91%) rotavirus patients were treated with intravenous fluids. G1P[8] was the predominant genotype during both years of surveillance, accounting for 133/222 (60%) of genotyped cases. Conclusion: Rotavirus is a major cause of hospitalization due to severe AGE in children <5 years of age in Tajikistan, accounting for >40% of cases. Continued, enhanced rotavirus surveillance may allow documentation of changes in rotavirus disease burden following vaccine introduction and assessment of vaccine effectiveness.